Prishvin and Stalin: Artistic Image of the Leader in Writer’s Work - A. M. Podoksenov; V. A. Telkova (Научный диалог)
The relevance of the study is due to the fact that the subject of the article is the question of who was the real prototype of the Chekist Sutulov in Prishvin’s novel “Tsar’s road”, which has not yet been considered in the history of foreign affairs. It is shown that in Russian literature it is difficult to find master of the pen, whose work would be to the same extent conditioned by the influence of the ideological and political context. The novelty of the research lies in the fact that for the first time an attempt was made to show how, through the artistic image of the Chekist Sutulov, one of the main characters of the novel “Tsar’s Road”, Prishvin seeks to reflect the ideo-logical and political attitudes, characteristic features of behavior, style of thinking and speech of Stalin. Particular attention is paid to the analysis of the 18-volume “Diary” of the writer, which was not previously published due to censorship restrictions, which became available to the reader only in the post-Soviet period. It is shown that, through the artistic image of Sutulov, Prishvin gives his personal assessment of Stalin’s role in the development of the state, striving to artistically faithfully and truthfully reflect the characteristic features of that atmosphere of economic, political and spiritual super-tension in which Soviet society lived in the 1930s on the eve of the Great Patriotic War.